(untitled) (Journal of Computational Mathematics, 2004)
We propose in this paper an alternating A-φ method for the quasi-magnetostatic eddy current problem by means of finite element approximations. Bounds for continuous and discrete error in finite time are given. And it is verified that provided the time step τ is sufficiently small, the proposed algorithm yields for finite time T an error of O(h+τ^1/2) in the L^2-norm for the magnetic field H(= μ^-1 abla × A), where h is the mesh size, μ the magnetic permeability.